Development of a TaqMan One-Step Quantitative PCR Assay for the Simultaneous Detection of Novel Goose Parvovirus and Novel Duck Reovirus - Yimin Wang; Yong Wang; Zhuangli Bi; Jinbin Wang; Gang Wang; Xin Ru; Chunchun Meng; Jie Zhu; Guangqing Liu; Chuanfeng Li (Microorganisms)
The novel goose parvovirus (NGPV) and the novel duck reovirus (NDRV) are pathogens that can substantially affect the growth and development of ducklings, causing considerable economic losses to duck farms. Therefore, a timely, rapid, accurate, and high-throughput diagnosis and identification of viral infections are critical for preventing the spread of epidemics. In this study, a TaqMan probe-based duplex one-step RT-qPCR was established for the simultaneous detection and qualitative and quantitative identification of the two viruses. It demonstrated greater sensitivity than conventional PCR, detecting as low as 2.42 copies/μL of NGPV genome and 70.1 copies/μL of NDRV genome. Additionally, it exhibited remarkable specificity, responding exclusively to the nucleic acids of target pathogens. It also demonstrated excellent reproducibility and availability, particularly in clinical settings, with a coinfection detection rate of 13.3%, contributing to the development of NGPV- and NDRV-testing technologies.